Climate shelters in the Global South: bridging a critical research gap in urban climate adaptation - Cavaco, Isabela Carmo; Campello Torres, Pedro Henrique (Frontiers in Built Environment, 2025)
This study investigates how climate shelters are addressed in academic literature, particularly in Global South countries. The research questions whether studies exist on this topic in the Global South and how the concept is discussed globally. It hypothesizes that, while climate shelters are gaining attention due to increasing climate extremes, academic research from the Global South is still limited. The objective is to present a state of the art on climate shelter studies and examine their presence in Southern contexts. A systematic review following the PRISMA protocol was conducted across five databases, emphasizing sources in Portuguese and Spanish. From 59 texts screened, 26 were analyzed. Results show most studies are concentrated in Europe, with few relevant publications from the Global South. This reveals a research gap but also emerging practices in countries like Argentina and Chile. Scientifically, the study updates the literature; socially, it highlights the urgency of context-based adaptation strategies.